Из материалов для комментария к «Капитанской дочке» (26–42) [Notes and Queries on _The Captain’s Daughter_ (26–42)] - Ospovat, Alexander (Slavica Revalensia, 2023)
The following notes highlight some of the structural patterns and textual fragments of Alexander Pushkin’s Captain’s Daughter overlooked by previous scholarship. Thus, I address the narrative strategy of shifting a character’s attributes so that the character’s initial connotations are seamlessly transformed into their opposites. This corresponds to the novel’s overall narrative principle of relativizing the seemingly obvious and stable. Additionally, I explore some of the narrative formulas specific to the historical novel, and comment on some of the historical information on the everyday life and social realities of 18th-century Russia contained in The Captain’s Daughter (the various forms of currency used by the different classes; Pugachev’s military equipment, etc.).